2004
DOI: 10.2139/ssrn.504445
|View full text |Cite
|
Sign up to set email alerts
|

Tourism, Trade and Domestic Welfare

Abstract: Tourism has been regarded as a major source of economic growth and a good source of foreign exchange earnings. Tourism has also been considered as an activity that imposes costs on the host country. Such costs include increased pollution, congestion and despoliation of fragile environments and intra-generational inequity aggravation. One aspect that has been ignored is the general equilibrium effects of tourism on the other sectors in the economy. These effects can be quite substantial and should be taken into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 41 publications
1
54
0
2
Order By: Relevance
“…Despite the potential economic benefits of tourism, a number ofstudies have notednegative externalities of tourism development, such asenvironmental degradation because of overexploitation of natural resources (Capó et al, 2007;Schubert, 2010), economic impoverishment of the resident population (Chao et al, 2006;Nowak et al, 2003), Dutch disease effects 1 (Capó et al, 2007;Holzner, 2005), loss of cultural and social values of the host community (Cooper et al, 1993), and the highly volatile nature of tourism receipts (Ghalia and Fidrmuc, 2016). 2 In a similar vein, and observed that tourism activity negatively affected Chinese economic growth, principally because of weak institutions, price volatility and the crowding out of human capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the potential economic benefits of tourism, a number ofstudies have notednegative externalities of tourism development, such asenvironmental degradation because of overexploitation of natural resources (Capó et al, 2007;Schubert, 2010), economic impoverishment of the resident population (Chao et al, 2006;Nowak et al, 2003), Dutch disease effects 1 (Capó et al, 2007;Holzner, 2005), loss of cultural and social values of the host community (Cooper et al, 1993), and the highly volatile nature of tourism receipts (Ghalia and Fidrmuc, 2016). 2 In a similar vein, and observed that tourism activity negatively affected Chinese economic growth, principally because of weak institutions, price volatility and the crowding out of human capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yapılan mevcut çalıĢmalarda ise kısaca turizm piyasasının genel anlamda yakınsayıp yakınsamadığı araĢtırılmıĢ-tır. Bu bağlamda, turizm alanında yapılan çalıĢmaların önemli bir kısmının genellikle turizmin ekonomiye katkılarını ölçmeye çalıĢtıkları görülmektedir (Hazari & Sgro, 1993Sgro, -1995Modeste 1995;Balaguer & Jorda 2002;Durbarry 2004;Nowak et al 2004;Gökovalı & Bahar, 2006;Bahar & Bozkurt, 2010).…”
Section: Teorik Ve Ampirik Literatür Taramasıunclassified
“…Narayan (2004) uses a computable general equilibrium (CGE) model to assess the long-run impact of a 10% increase in tourist expenditure on Fiji's economy. Nowak et al (2003) present a model that captures the interdependence between tourism and the rest of the economy and find that the tourist boom may 'immiserize' the residents when the non-traded tourism sector is more labour-intensive than the agricultural traded sector. Zhou et al (1997) use a CGE model to examine the impacts of tourism on the economy of a region.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A few studies exist on the impact of tourism on prices (and other variables, such as gross domestic product, employment and exchange rates) from a macroeconomic point of view (Hazari and Ng, 1993;Adams and Parmenter, 1995;Zhou et al, 1997;Nowak et al, 2003;Narayan, 2004;Chao et al, 2005Chao et al, , 2006. These studies rely on strong assumptions rather than on empirical results (see the 'theoretical framework' section).…”
mentioning
confidence: 99%